PRAGMATIC AND STYLISTIC MARKERS OF SUBJECTIVITY IN W.S.MAUGHAM’S “RAIN” - Narzullayeva , Mohina; Chekulay , Igor (Scientific practical conference, 2025)
This paper delves into the style and pragmatics of “Rain” by W.S.Maugham, emphasizing the linguistic and narrative techniques of authorial subjectivity. This research theorizes the stylistic elements and the pragmatic speech acts of presumption and Grice’s Cooperative Principle. The focus is on the evaluative lexis of narrative, irony, and dialogue. It is argued that Maugham creates a striking balance between empathy and moral condemnation, leading the reader to emotionally support and morally criticize Sadie Thompson and Davidson, respectively. The new prose is oriented toward a gentle postulation of the obstacles of dogmatism and a more profound awareness of human interplay.